ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEMUNGKINAN TERJADINYA FINANCIAL DISTRESS (Studi Pada Perusahaan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2011 - 2015) - Alexanders, Miechael; Kamaliah, Kamaliah; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze the effect of Profit, Cash Flow, Liquidity proxied with Current Ratio, Profitability proxied with ROA and Financial Leverage which proxied with DER in predicting financial distress condition experienced by real estate company listed on BEI at Year 2011-2015. Data were analyzed by using logistic regression method. Based on the feasibility test can be explained that the results of 175 data of real estate companies listed on the Stock Exchange in 2011-2015 by using logistic regression, feasible to analyze the prediction of troubled conditions or financial distress in the real estate company sector listed on BEI In 2011-2015. The results of hypothesis analysis and testing of this study found that partially Profit and Financial Leverage proxied with DER does not significantly influence the prediction of the condition of financial distress in real estate companies listed on the Stock Exchange in 2011-2015, while the variable Cash Flow, Liquidity proxies with Current Ratio, and Profitability proxyed by ROA have a significant effect to prediction of condition of distress (financial distress) at real estate company listed on BEI in year 2011-2015. Variability of dependent variable (problem condition or financial distress condition) which can be explained by variability of independent variable (Profit, Cash Flow, Liquidity proxyed with Current Ratio, Profitability proxyed by ROA and Financial Leverage proxyed by DER) is 61 , 2% while the rest, ie 38.8% is explained by other variables outside the model.Keywords : Profit, Cash Flow, Liquidity, Profitability, Financial Leverage and Financial Leverage